2002
DOI: 10.1002/art.10493
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐engineered composites for the repair of large osteochondral defects

Abstract: Objective. To test the hypothesis that engineered cartilage can provide a mechanically functional template capable of undergoing orderly remodeling during the repair of large osteochondral defects in adult rabbits, as assessed by quantitative structural and functional methods.Methods. Engineered cartilage generated in vitro from chondrocytes cultured on a biodegradable scaffold was sutured to a subchondral support and the resulting composite press-fitted into a 7-mm long, 5-mm wide, 5-mm deep osteochondral def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
219
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(224 citation statements)
references
References 39 publications
3
219
1
1
Order By: Relevance
“…This is done in an effort to provide an environment that can support the existing host cell population thereby circumventing the costly and cumbersome requirement of in vitro pre-culture prior to implantation. Numerous scaffolds utilised in this area consist of synthetic materials, such as poly(e-caprolactone) (PCL) [12], poly(glycolic acid) (PGA) [13] and poly(lactide-co-glycolide) (PLGA) [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done in an effort to provide an environment that can support the existing host cell population thereby circumventing the costly and cumbersome requirement of in vitro pre-culture prior to implantation. Numerous scaffolds utilised in this area consist of synthetic materials, such as poly(e-caprolactone) (PCL) [12], poly(glycolic acid) (PGA) [13] and poly(lactide-co-glycolide) (PLGA) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, slow degradation rates, harmful degradation by-products, poor cell attachment, inability to direct cellular differentiation, and reduced immunogenicity have led to limited long-term success following in vivo application [13]. Natural materials, including collagen [16,17] fibrin [18], hyaluronan [19], alginate [20] and agarose [21][22][23], have been widely investigated for use in osteochondral tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the articular surface can penetrate to the subchondral bone and such osteochondral defects are often associated with mechanical instability of the joint and warrant surgical intervention in order to prevent osteoarthritic degenerative changes [1]. Even in cases where lesions do not penetrate to the subchondral bone an osteochondral construct may be a more desirable implant as a bone-to-bone interface integrates better than a cartilage-to-cartilage interface [2].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies performed in rabbit (Ball et al, 2004;Grigolo et al, 2001;Schaefer et al, 2002), sheep (Kandel et al, 2006), or goat (Niederauer et al, 2000) aimed at investigating the outcome of cartilage or osteochondral repair using engineered cartilage. Cells were seeded in the scaffolds either directly after isolation or after an expansion phase and further pre-cultured in vitro for 48 h (Niederauer et al, 2000), 7 d (Ball et al, 2004), 4 to 6 weeks (Schaefer et al, 2002), or 8 weeks (Kandel et al, 2006) before implantation in an orthotopic site. With only one exception (Niederauer et al, 2000), an improved healing was observed when cells were added to the scaffolds as compared to implantation of cell-free materials.…”
Section: Introductionmentioning
confidence: 99%